Anularea actelor juridice în procedura insolvabilităţii - Chirtoacă, Rodica (CEP USM, 2024)
After the initiation of the insolvency procedure, the authorized administrator is entitled to undertake, in the interest of creditors, a series of measures aimed at restoring the debtor’s assets by reclaiming the assets that were alienated to the detriment of creditors. These measures can be categorized into two types: measures aimed at restoring the debtor’s assets, which were diminished by fraudulent acts, and measures for managing the debtor’s portfolio of contracts. The annulment of legal acts in the insolvency procedure is of interest to the creditors of the debtor, as they find themselves unable to satisfy their claims. This work aims to provide a general analysis of situations in which the debtor’s acts may fall under the provisions of Articles 104-105 of Law no. 149/2012. Additionally, it focuses on the conditions under which legal action can be brought before the insolvency court. In this study, research methods such as comparative analysis, deductive reasoning, and inductive reasoning were employed to ensure the achievement of the objectives formulated regarding the institution under investigation. The main research tools used in this scientific endeavor included scientific publications in the field of bankruptcy, normative acts, and judicial practice.
CANCELLATION OF LEGAL DEEDS IN INSOLVENCY PROCEEDINGS
Keywords: acts; creditor; fraudulenly; interest; suspect